Accelerations or the earthquake of February 27, 2018 obtained by the accelerographic network of the Santiago de Cuba city - Sandra Y. Rosabal-Domínguez; Raúl Palau-Clares; Manuel Cutié-Mustelier; Ricardo Oliva-Álvarez; Zulima Rivera-Álvarez; Madelín Villalón-Semanat (Minería y Geología, 2021)
For the first time, records from the perceptible earthquake of greater magnitude in 2018 were obtained and analyzed with 13 accelerograph networks from Santiago de Cuba city. A procedure that allows achieving isoacceleration schemes is used. Correlations with the local geology, and microzonation and reported seismic intensities are established. The maximum acceleration values in the horizontal component reached for the earthquake on February 27th, 2018 of magnitude 3.9 Richter were: ARAF with 12.10 cm/s2; AARA with 13.50 cm/s2; AKEN with 19.10 cm/s2 and AYEL with 48.60 cm/s2.